186k views
0 votes
Solve the equation -2(y - 1) = 9.
-11/2
7/2
11/2
-7/2

User CopyOfA
by
5.8k points

2 Answers

1 vote
Hope this helps !! Did it step by step
Solve the equation -2(y - 1) = 9. -11/2 7/2 11/2 -7/2-example-1
User Rasheema
by
5.0k points
4 votes

Answer:

-7/2

Explanation:

Use distributive property: a(b +c) = a*b +a*c

-2(y-1) = 9

y*(-2) - 1*(-2) = 9

-2y + 2 = 9 {Subtract 2 from each side}

-2y = 9 - 2

-2y = 7 {Divide each side by -2}

y = 7/-2

y = -7/2

User Glassomoss
by
5.2k points